Transversus Abdominis Plane Block for Postoperative Analgesia in Patients Undergoing Total Laparoscopic Hysterectomy: A Randomized, Controlled, Observer-Blinded Trial. (August 2016) - Ghisi, Daniela; Fanelli, Andrea; Vianello, Federico; Gardini, Marco; Mensi, Giulio; La Colla, Luca; Danelli, Giorgio
Abstract : BACKGROUND: In this randomized, controlled, observer-blinded study, we evaluated analgesia provided by transversus abdominis plane (TAP) block after elective total laparoscopic hysterectomy in terms of reduced postoperative morphine consumption as the primary end point. METHODS: Fifty-two patients were randomly divided into 2 groups: patients in group T (TAP, n = 26) received an ultrasound-guided bilateral TAP block with 40 mL of 0.375% levobupivacaine and morphine patient-controlled analgesia, whereas patients in group C (control, n = 26) received morphine patient-controlled analgesia. Secondary outcomes included pain measurements (Numeric Rating Scale from 0 to 10) during the first 24 hours postoperatively, times to postanesthesia care unit discharge, times to surgical ward discharge, incidence of postoperative nausea and vomiting, functional capacity measurements in terms of 2-minute walking test, and first oral solid intake. RESULTS: Demographic and anthropometric variables were similar in the 2 groups. The total dose of morphine consumed by patients during postanesthesia care unit stay was 6 (0–8) mg in group T vs 8 (5.5–8.5) mg in group C ( P = 0.154). Postoperative morphine consumption during the first 24 hours was 10.55 ± 10.24 mg in group C vs 10.73 ± 13.45 mg in group T ( P = 0.950). The 95% confidence interval of the difference between means of 24-hour morphine consumption was −7.45 to +7.09. The 2 groups were comparable. There were no significant differences in secondary outcome variables between groups. CONCLUSIONS: TAP block did not reduce morphine consumption during the first postoperative 24 hours after elective total laparoscopic hysterectomy. Abstract : Published ahead of print April 12, 2016